P296 The role of Candida in acute pancreatitis: A disregarded pathogen. (20th September 2022) - Srivastava, Smriti; Sharad, Neha; Ningombam, Aparna; Kiro, Vandana; Varma, Sharin; Malhotra, Rajesh; Mathur, Purva
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Background: Acute pancreatitis is often complicated by infection of peri-pancreatic necrotic tissue. The infectious etiology commonly involves gram negative enteric bacilli and enterococci. Role of Candida species has remained debatable, despite being isolated in pure or mixed cultures in specimens. We evaluated patients with acute pancreatitis with Candida infection over a duration of 4 years for assessment of risk and prognostic factors. Objectives: To determine the prevalence and role of Candida infection in patients of acute pancreatitis and ascertain the species distribution and risk factors. Methods: This study was conducted including adult patients who were admitted to gastro-surgery department and had clinical suspicion of peri-pancreatic fungal infection. Specimens included peri-pancreatic fluid collection obtained intra-operatively or aspirated USG-guided, drain fluid and blood. In addition to aerobic bacterial culture, fungal cultures were performed availing standard mycological procedures. Candida infections were categorized into true and possible as per Chakraborty et al. with some modifications. True Candida infection of pancreatic tissue was considered when yeast cells were seen and grown in pure or mixed culture from Peri-pancreatic fluid obtained intra-operatively, or USG-guided aspirate, or Abdominal drain fluid and blood culture. Possible Candida infection of pancreatic tissue was considered when Candida spp were isolated from Abdominal drain effluent (at least two samples) in postoperative patients, or Candida spp grown in only in blood culture. Relevant patient information was obtained from hospital information system. Data were analyzed by SPSS 20 statistical software and MS Excel. Results: A total of 14 cases were identified amongst which 6/14 (42.9%) had true Candida infection whereas possible Candida infection was seen in 8/14 (57.1%) patients. Out of these, C. tropicalis was the predominant species seen in 9/14 (64.3%) whereas C. albicans was seen in 4/14 (28.6%). One isolate of C. auris was identified. Patients with C. tropicalis infection showed higher mortality (6/9, 66.7%) as compared with patients with other Candida species, in whom 20% (1/5) mortality was noted. Acknowledging limitations inherent to retrospective data extraction, we delineated some of the possible risk factors predisposing to Candida infection, given in Table 1. Conclusion: Role of Candida species in the pathogenesis of adjacent tissues in case of acute pancreatitis has been neglected in past, but now being increasingly recognized. C. tropicalis is the commonest isolate in our study and carries very high mortality. Screening for Candida spp should be carried out in these patients in view of starting antifungal treatment at the earliest possible so that proper diagnosis and management can be undertaken.